2019
DOI: 10.3389/fnhum.2019.00193
|View full text |Cite
|
Sign up to set email alerts
|

Low Prefrontal GABA Levels Are Associated With Poor Cognitive Functions in Professional Boxers

Abstract: Cognitive dysfunction has long been recognized as a frequently observed symptom in individuals with repetitive mild traumatic brain injury (rmTBI) such as professional boxers. The exact neurobiological mechanisms underlying this cognitive deficit have not yet been identified, but it is agreed upon that the prefrontal cortex (PFC) is one of the most commonly affected brain regions in professional boxers. Noting the pivotal role of the two major brain metabolites in human cognitive functions, γ-aminobutyric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Animal studies confirmed the acute metabolic response to impact, showing that 1 h after actual traumatic brain injury the balance between excitatory and inhibitory neurotransmitters is altered (Harris et al, 2012). The chronic GABAergic response in sport was confirmed using spectroscopy in boxers in this issue (Kim et al, 2019), and previously in American football players by Tremblay et al (2014) assessed through spectroscopy as well as TMS assessed cortical silent period. They found a complex but interesting pattern of results suggesting that indeed the normal balance between GABA mediated inhibition and excitation was altered in the players who sustained a concussion on average 3 years prior.…”
Section: Discussionsupporting
confidence: 64%
“…Animal studies confirmed the acute metabolic response to impact, showing that 1 h after actual traumatic brain injury the balance between excitatory and inhibitory neurotransmitters is altered (Harris et al, 2012). The chronic GABAergic response in sport was confirmed using spectroscopy in boxers in this issue (Kim et al, 2019), and previously in American football players by Tremblay et al (2014) assessed through spectroscopy as well as TMS assessed cortical silent period. They found a complex but interesting pattern of results suggesting that indeed the normal balance between GABA mediated inhibition and excitation was altered in the players who sustained a concussion on average 3 years prior.…”
Section: Discussionsupporting
confidence: 64%
“…Experimental data have indicated that TBI can cause reduced expression of GAT at 24 h post-injury [68]. Magnetic resonance spectroscopy (MRI) has shown lower GABA levels in the prefrontal cortex associated with memory deficits in professional boxers repetitive mild TBI [69]. Utilizing this technique, recent work has indicated region and time-specific changes in the GABA showing reduced levels in the cerebral cortex at 72 h and two-week post-mild TBI [70].…”
Section: Gaba (γ-Aminobutyric Acid)mentioning
confidence: 99%
“…Recent studies have also found that inhibitory deficits in the medial prefrontal cortex in a prepubescent FXS mouse model (Kramvis et al, 2020). Multiple clinical 1 H-MRS studies measuring GABA in various adult populations have found that decreased GABA concentrations in the prefrontal cortex, dorsolateral prefrontal cortex, or frontal cerebrum are correlated with decreased cognitive function and working memory task performance (Yoon et al, 2016;Porges et al, 2017;Kim et al, 2019). Another 1 H-MRS clinical study found a positive correlation between visual intelligence and GABA concentration in the primary visual cortex (Cook et al, 2016).…”
Section: Discussionmentioning
confidence: 99%